Screening for bioactive secondary metabolites in Sri Lankan medicinal plants by microfractionation and targeted isolation of antimicrobial flavonoids from Derris scandens. (10th January 2020) - Mohotti, Supun; Rajendran, Sanjeevan; Muhammad, Taj; Strömstedt, Adam A.; Adhikari, Achyut; Burman, Robert; de Silva, E.D.; Göransson, Ulf; Hettiarachchi, C.M.; Gunasekera, Sunithi
Abstract: Ethnopharmacological relevance: Sri Lanka is known to have very diverse flora. Many of these species are used for plant-based remedies, which form the integral part of two Sri Lankan systems of traditional medicine, Ayurveda and Deshiya Chikitsa. Despite their widespread use, only a limited number of studies have probed into the scientific evidence for bioactivity of these medicinal plants. Such studies rarely progress to the identification of bioactive natural products. Aim of the study: The primary aim was to develop a bioactivity screening method and apply it to 50 Sri Lankan medicinal plants where antimicrobial properties could be relevant for its traditional use. The subsequent aim was the progression into defining and characterising potent isolates within targeted compound classes from such plants, i.e. Derris scandens and its antimicrobial flavonoids. Material and methods: The plant collection comprised 24 species of Fabaceae, 15 Rubiaceae, 7 Solanaceae and 4 Cucurbitaceae plants. These 50 species were collected based on their ethnopharmacological importance and use in Sri Lankan traditional medicine. Crude extracts from each species were initially subjected to radial disc diffusion and microdilution assays. Subsequently, aqueous extracts of all plants were microfractionated in deep well plates using reversed-phase HPLC. Fractions were tested for antibacterial and cytotoxic activities and masses of target bioactive compounds were identified using mass spectrometry. Bioactive compounds with the masses identified through microfractions were isolated from Derris scandens using reversed-phase HPLC. The isolated pure compounds were characterised using LC-MS and NMR. Results: Crude aqueous extracts from 19 species showed activity against Gram-positive bacteria ( Staphylococcus aureus and Bacillus cereus ) in the radial disc diffusion assay. Crude aqueous extracts from 34 plant species and organic extracts from 46 plant species were active against S. aureus (≤4 mg mL -1 ) in the microdilution assay. Microfractionation demonstrated antibacterial activity for 19 plants and cytotoxicity for 6 plants. Furthermore, target bioactive compounds and their molecular ions were identified during microfractionation. Dalpanitin and vicenin-3, two of the flavonoids isolated from Derris scandens gave MICs of 23 μg mL -1 against S. aureus . Dalpanitin also exhibited relevant MICs on Gram-negative bacteria (94 μg mL -1 against Escherichia coli and Pseudomonas aeruginosa ). Conclusion: The microfractionation protocol developed in this study enabled time-efficient screening of many plants species, using a small quantity of sample material. In addition, microfractionation served as a guiding tool for identifying individual antimicrobial compounds. Through this process, flavonoids were isolated from Derris scandens, out of which dalpanitin and vicenin-3 showed activity in the low micromolar range. The high hit rate for in vitro antibacterial properties from this ethnopharmacologically guided sample collection gives credence to Sri Lankan traditional herbal medicine as a source for drug discovery. Graphical abstract: Image 1